(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
The Imposto sobre Propriedade de Veículos Automotores (IPVA) is the responsibility of the states and the Federal District, that is, the tax is governed by state legislation. There were discussions in the Supreme Federal Court (STF) regarding the incidence of this tax on vessels and aircraft, however, the STF decided to exempt the collection of IPVA on the assets in question. The purpose of this research is the estimated presentation of the tax disbursement of air transport companies if the collection of IPVA on their aircraft was instituted. With that, this research searched in the financial statements of the air transport companies Azul and Gol, the respective values corresponding to the possessions of their aircraft. Upon this amoun t was applied and calculated at the IPVA rate. The rate used corresponds to the host state of each airline Azul and Gol, which are São Paulo and Rio de Janeiro respectively. Both states have a 4% rate for levy IPVA for land vehicles. The estimated tax disb ursement that the air transport companies Azul and Gol build in 2019 regarding the collection of IPVA on their aircraft would be R 261.415,84 and R 131.057,04 respectively. For companies, this tax would be seen as an additional tax liability to be paid, in others words, for them it would be considered negatively.However for the states that received this amount, it would help to strengthen their finances.